(Re) lendo o cotidiano: proposta de material didático para a educação infantil - (:unkn) unknown (Universidade Federal de Goiás, 2019)
The present text is a research developed in the Program of Post-Graduation in History, Professional Masters, of the Federal University of Goiás - Regional Catalão. The objective is to reflect on the issues of gender and diversity in early childhood education, as well as to present a didactic material elaborated with inclusive and plural. The central proposal of the research is to problematize the established standards and to oppose the construction of knowledge in the same way as it does in the 21st century, marked by norms and heteronormative patterns that are present in schools, especially those in early childhood education. Methodologically, I opted for an elaboration aimed at teachers, who may have access to a different look at pedagogical practices.The material is also directed to the students, who will establish contact with a new reference in the treatment of the issues of gender and diversity, in a non-hegemonic and naturalized way. The results obtained in this study allow me to affirm that access to a non-normatized perspective of being contributes to the construction of a counter-hegemonic education, and indicates possibilities for the breaking of paradigms and for a more human, diverse and plural formation.
Keywords: Materiais didáticos; Gênero e sexualidade; Práticas escolares; Didactic materials; Gender and sexuality; School practices; CIENCIAS HUMANAS::HISTORIA